The foret of the fortune-tellers... Or the intrigues of the social interaction among the children in the kindergarten around the cultured books - Maria Manuela Martinho Ferreira; Cristina Maria Löbe Guimarães Madureira (Universidade Federal de Santa Catarina, 2008)
Based on an interactive episode of the notes taken from the field of ethnographic work done with a group of 10 children between 5 and 6 years of age, in the context of kindergarten (JI), this article makes contributions of Sociology of Children to account of the social uses that children make the picture books, when they use them on their own initiative, and the ways in which i) show your agency in building a social identity in the group and, ii) ressignificam symbolically the picture books, objects of adult cultural production aimed at children, iii) are used symbolically and strategically power relations and sociability that are playing in their midst. By redefining the illustrated book as an object for use by children, aims to contribute to awareness of the need to i) reassess the role of books in daily life of the times and spaces of JI, ii) review the practice of use of the illustrated book with children in institutional context, iii) reconfigure the book as object producer of cultural meanings intersubjectivos iv) reconfigure the illustrated book as being traded on the social and cultural appropriations by the children who use it, the group of peers and, finally V) review the concepts of childhood that this choice and selection of printed materials that are available for use by children.